Management of Tahfizhul Qur'an Curriculum Development at the Tahfizh Putri Manba'ul Qur'an Islamic Boarding School - Septri Larasati; Andi Murniati (Penerbit Hellow Pustaka, 2024)
This development research aims to design the management of the Tahfizh Al-Qur'an program. This study uses the Borg and Gall research development method. The development design uses the inverted Taba model. The seven-step model that is applied is: The first stage in the management of developing the curriculum for the tahfizhul Qur'an program is diagnosing needs. The results of diagnosing the needs of the tahfizhul Qur'an program through field observations and documentation studies are in the form of: Implementation of tahfizhul Qur'an using varied and fun methods, setting targets for memorizing material, implementing effective evaluations. The second stage is formulating goals. The third stage is choosing content / material. After the objectives are formulated, then choose the content/material for tahfizhul Qur'an. The fourth stage organizes the content/material. The material for the tahfizhul Qur'an program that has been determined is compiled and classified into six levels for six years starting from MTs to MA level. The fifth stage is choosing a learning experience, the learning experience includes memorizing the Al-Qur'an, depositing the memorization to the teacher and doing murajaah. The sixth stage is organizing the learning experience, the learning experience is packaged into activity packages for the tahfizhul Qur'an program. The seventh stage is evaluating. evaluation of the tahfizhul Qur'an program which includes daily evaluations, monthly evaluations, semester evaluations and year-end quarantine for those who have completed memorizing 30 juz.